2007
DOI: 10.2334/josnusd.49.115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CPP-ACP paste on tooth mineralization: an FE-SEM study

Abstract: Milk and milk products, such as cheese, have been shown to exhibit anticariogenic properties in human and animal models. CPP-ACP shows an anti-caries effect by suppressing demineralization, enhancing remineralization, or possibly a combination of both. The purpose of this study was to evaluate the effect of CPP-ACP paste on demineralization by observing the treated tooth surface using an FE-SEM. The specimens were prepared by cutting enamel and dentin of bovine teeth into blocks. A few specimens were stored in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
0
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(141 citation statements)
references
References 22 publications
5
122
0
14
Order By: Relevance
“…Além disso, o tipo de cálcio na composição do agente clareador testado (gluconato de cálcio) não é o mesmo CPP-ACP encontrado na maioria dos estudos 28,29 . Em um estudo que usou CPP-ACP diluído no agente clareador, foi encontrada diminuição na microdureza do esmalte 30 .…”
Section: Discussionunclassified
“…Além disso, o tipo de cálcio na composição do agente clareador testado (gluconato de cálcio) não é o mesmo CPP-ACP encontrado na maioria dos estudos 28,29 . Em um estudo que usou CPP-ACP diluído no agente clareador, foi encontrada diminuição na microdureza do esmalte 30 .…”
Section: Discussionunclassified
“…This suggests the preventive role of CPP-ACP in enamel demineralisation (Yamaguchi et al, 2007). Ferrazzano et al (2007), used the weight loss of the samples to determine demineralisation in their study.…”
Section: Cpp-acp Effect On Demineralisationmentioning
confidence: 99%
“…A study using sonic velocity to quantify bovine enamel mineralisation reported that using a 1:10 dilution of Tooth Mousse enhances the mineralisation of enamel under acidic conditions (0.1 M buffered lactic acid) for 10 minutes twice a day for 10 days (Yamaguchi et al, 2007).…”
Section: In Vitro Remineralisation Studiesmentioning
confidence: 99%
“…Enamel microabrasion together with prolonged use of CPP-ACP based paste is useful for treating white spot enamel lesions. 21 Method of application of topical cream: It can be applied directly with clean finger onto the teeth, smeared over all surfaces, and left in place to slowly dissolve overnight. Any material that is swallowed is completely safe and will contribute toward dietary calcium.…”
mentioning
confidence: 99%